2019
DOI: 10.1111/fwb.13464
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and host diet jointly influence the outcome of infection in a Daphnia‐fungal parasite system

Abstract: Climate change has the potential to shape the future of infectious diseases, both directly and indirectly. In aquatic systems, for example, elevated temperatures can modulate the infectivity of waterborne parasites and affect the immune response of zooplanktonic hosts. Moreover, lake warming causes shifts in the communities of primary producers towards cyanobacterial dominance, thus lowering the quality of zooplankton diet. This may further affect host fitness, resulting in suboptimal resources available for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 87 publications
3
35
0
Order By: Relevance
“…Increases in temperature and pathogen exposure, however, will not only shape host thermal tolerance, but will also drive changes in all aspects of a host's phenotype, including development, growth, fecundity and population-level processes (e.g. [9,[14][15][16][17]). Population persistence will therefore be shaped by how temperature change and pathogen exposure directly interact to shift multiple facets of a host's phenotype, in addition to the complex role that temperate plays in driving pathogen transmission strategies [18][19][20] and host-pathogen interactions more broadly [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in temperature and pathogen exposure, however, will not only shape host thermal tolerance, but will also drive changes in all aspects of a host's phenotype, including development, growth, fecundity and population-level processes (e.g. [9,[14][15][16][17]). Population persistence will therefore be shaped by how temperature change and pathogen exposure directly interact to shift multiple facets of a host's phenotype, in addition to the complex role that temperate plays in driving pathogen transmission strategies [18][19][20] and host-pathogen interactions more broadly [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the impacts of temperature and pathogen exposure often focus on their effects on individual host traits (e.g. [14][15][16][17]). However, organisms are comprised of multiple correlated traits that together form the integrated phenotype [26].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that low‐quality diet (cyanobacteria) could reduce the output of Daphnia gut parasites (Manzi et al., 2020 ). Besides, food with high C:P ratios can significantly reduce bacterial infection rates in daphnids (Frost et al., 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that low-quality diet (cyanobacteria) could reduce the output of Daphnia gut parasites (Manzi et al, 2020).…”
Section: How Do Daphnia Deal With Stoichiometric Constrains? Lessons From Transcriptomic Datamentioning
confidence: 99%
“…A recent study showed that low-quality diet (cyanobacteria) could reduce the output of Daphnia gut parasites [30]. Besides, food with high C : P ratios can signi cantly reduce bacterial infection rates in daphnids [31].…”
Section: How Do Daphnia Deal With Stoichiometric Constrains? Lessons mentioning
confidence: 99%